Pemberdayaan UMKM Desa Cihampelas melalui Edukasi dan Pelatihan Pemasaran Digital - Dzilla Khoerunnisa; Annisaa' Siti Shalihah; Fajar Sidik; Widad Ristia Zulkha; Charolina Charolina; Syifa Utami Asrianty; Deni Nugraha; Kayla Salsabilla; Putri Marshanda; Teguh Mulya Sandi; Yudi Daryadi (BADAN PENERBIT STIEPARI PRESS, 2025)
Empowering micro, small, and medium enterprises (MSMEs) through digital marketing training is one of the tangible contributions made by community service students (KKN) in Cihampelas Village. This program was designed to address the challenges faced by small business owners in promoting their products in the digital era. The main activities included providing education on digital marketing strategies, designing business logos that represent product identity, and assisting in branding so that MSMEs can adapt to technological developments. In addition, students offered technical guidance on the use of social media platforms such as Instagram, Facebook, and WhatsApp Business as effective promotional tools. Special assistance was also provided to introduce the use of Google Maps, enabling local businesses to become more visible and easily accessible to potential customers. Through an interactive approach, the training emphasized not only theoretical knowledge but also hands-on practice that participants could directly apply to their businesses. The outcomes of the program revealed improvements in digital literacy, greater awareness of the importance of business identity, and enhanced skills in utilizing digital platforms for promotion. Participants’ enthusiasm was evident through their active involvement in discussions and practice sessions, indicating that the need for digital skills among MSMEs is very high. Although there were still some limitations in technical mastery, this program successfully created a positive impact and opened opportunities for sustainable development of MSMEs in Cihampelas Village. It is expected that, after the program, local entrepreneurs will continue to develop their digital skills, allowing them to compete and expand their market reach in an increasingly competitive global environment.